2018
DOI: 10.3146/ps17-16.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Seeding Rate and Cultivar Effects on Peanut (Arachis hypogaea L.) Seeded in 76-cm Row Spacing

Abstract: Standard row spacing for peanut (Arachis hypogaea L.) in Georgia is 91-cm in a single-row pattern. Narrower row spacings are often used in crops grown in rotation with peanut. Therefore, converting peanut to narrower row spacing may be easier and beneficial to some growers if cultivars and seeding rates can be identified that can be grown in narrow rows without a reduction in yield and grade. Based on current University of Georgia recommendations, peanut is typically planted at 19 seed/m with a 91-cm row spaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Maximum yields and greater economic viability have been observed with densities from 15.7 to 20.0 peanut seeds m −2 in the United States (Oakes et al., 2020; Plumblee et al., 2018). In Brazil, studies with densities of runner‐type peanut cultivars are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Maximum yields and greater economic viability have been observed with densities from 15.7 to 20.0 peanut seeds m −2 in the United States (Oakes et al., 2020; Plumblee et al., 2018). In Brazil, studies with densities of runner‐type peanut cultivars are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Leaf area index in 2016 also presented higher values for twinrow peanut than single row when DOY< 60 (Figure 13A). A greater crop growth in twin-row peanut is also reported by Colvin et al (1985); Jaaffar andGardner (1988), andPlumblee (2015). Jaaffar and Gardner (1988) also linked the faster canopy closure of peanut in twin-row to its higher growth rate and light interception.…”
Section: Discussionmentioning
confidence: 60%
“…GA-06G is one of the most popular cultivars throughout southeastern U.S. and its ability to yield and grade well in different environments, different row spacing and seed rates may be the contributing factors for its widespread adoption (Plumblee et al, 2018;Tubbs et al, 2011). In three yr of the study, GA-12Y cultivar outperformed GA-06G in yields in six out of 10 observations when planted on different planting dates.…”
Section: Resultsmentioning
confidence: 92%
“…It is common for the cultivars to show differences in peanut grade (Faircloth and Prostko, 2010). Plumblee et al (2018) reported that peanut cultivars affected TSMK while seeding rate did not show any effect on peanut grade. The TSMK results obtained in our study are in accordance with other studies which observed higher grade for GA-06G and TUFRunner 297 and slightly lower grade for GA12Y (Branch 2007 and2013;Tillman 2018).…”
Section: Resultsmentioning
confidence: 99%